Cost-effectiveness of omalizumab for the treatment of moderate-to-severe uncontrolled allergic asthma in the United States. (2nd January 2020) - Sullivan, Patrick W.; Li, Qianyi; Bilir, S. Pinar; Dang, Joseph; Kavati, Abhishek; Yang, Ming; Rajput, Yamina
Abstract: Objective: Uncontrolled asthma is associated with considerable clinical burden and costs to payers and patients. US economic models evaluating biologics using data from clinical trials demonstrate high incremental cost-effectiveness ratios (ICERs), but the cost-effectiveness based on real-world treatment patterns is unknown. This analysis used real-world evidence to assess the cost-effectiveness of adding omalizumab to standard of care (SOC). Methods: A Markov model was applied to track patients' health states in 2-week cycles, comparing costs and treatment effects of SOC alone versus SOC + omalizumab over a lifetime (US payer perspective). Outcomes included exacerbation events, life years, quality-adjusted life years (QALYs), total costs, and an ICER. Patient characteristics, exacerbations, patient-reported outcomes, and work productivity were derived from the real-world PROSPERO (Prospective Study to Evaluate Predictors of Clinical Effectiveness in Response to Omalizumab) study. Published literature informed mortality, exacerbation-related disutility, and unit costs. Sensitivity analyses assessed model robustness. Results: Over a lifetime horizon, omalizumab was associated with an increase of 2.0 QALYs at a cost of US 148, 319 in patients with uncontrolled asthma (ICER of 75, 319/QALY gained) and a reduction in exacerbations of 6.0 events/patient. Accounting for responder status improved the ICER (70, 505/QALY); incorporating indirect costs further reduced the ICER. One-way and multivariate sensitivity analyses confirmed that the base case outcome was robust to variation in inputs. Conclusions: Based on real-world outcomes, omalizumab may be cost-effective for uncontrolled asthma from the US payer perspective. Including broader evidence on treatment discontinuation, caregiver burden, and oral corticosteroid reduction from real-world studies may better reflect the effects and value of omalizumab for all healthcare stakeholders.